Nitrogen Dioxide Selective Sensor for Humid Environments Based on Octahedral Indium Oxide - Domènech-Gil, Guillem; Gràcia, Isabel; Cané, Carles; Romano-Rodríguez, Albert (Frontiers in Sensors, 2021)
We report the growth of micrometer-sized In2O3 octahedral structures, which are next aligned in chains using dielectrophoresis on top of microhotplates with prepatterned electrodes and integrated heater to work as chemoresistive gas sensors. The devices are relatively fast (180 s), highly sensitive (response up to 256%), and selective toward NO2 in humid environments, showing little response to O2 and ethanol, and being completely insensitive to CO and CH4. The here-presented fabrication method can be easily extended as a cost-effective post-process in CMOS-compatible microhotplate fabrication and, thus, represents a promising candidate for indoor and outdoor air quality monitoring devices.